Enhancing the strain sensitivity of CoFe2O4 at low magnetic fields without affecting the magnetostriction coefficient by substitution of small amounts of Mg for Fe - Anantharamaiah, P. N.; Joy, Pattayil Alias (Physical Chemistry Chemical Physics, 2016)
Attaining high magnetostrictive strain sensitivity (d lambda/dH) with high magnetostriction strain (lambda) is desirable for sintered polycrystalline cobalt ferrite for various applications. It is shown that substitution of a small amount of Fe3+ by Mg2+ in CoMgxFe2-xO4 (x < 0.1) gives a comparable maximum magnetostriction coefficient to that of the unsubstituted counterpart, with large improvement in the strain sensitivity at relatively low magnetic fields. A large increase in the magnetostriction coefficient is obtained at low magnetic fields for the substituted compositions. The magnetostriction parameters are further enhanced by magnetic field annealing of the sintered products. The results are analyzed based on powder XRD, Raman spectroscopy, XPS and magnetic measurements and based on the results from these studies, the changes in the magnetostriction parameters are correlated with the changes in the cation distribution, magnetic anisotropy and microstructure.